Surgical treatment for colorectal cancer: analysis of the influence of an enhanced recovery programme on long-term oncological outcomes—a study protocol for a prospective, multicentre, observational cohort study - Javier Ripollés-Melchor; Ane Abad-motos; Alfredo Abad-gurumeta; Jose-M Ramirez-Rodriguez; Javier Martinez-Ubieto; Jose-L Muñoz-Rodes; Jose-R Rodriguez-Fraile; Jose-A Garcia-Erce; Javier Blanco-Gonzalez; Emilio Del Valle-Hernandez; Eugenia Centeno-Robles; Carolina Martinez-Perez; et al. (BMJ Open)
Introduction The evidence currently available from enhanced recovery after surgery (ERAS) programmes concerns their benefits in the immediate postoperative period, but there is still very little evidence as to whether their correct implementation benefits patients in the long term. The working hypothesis here is that, due to the lower response to surgical aggression and lower rates of postoperative complications, ERAS protocols can reduce colorectal cancer-related mortality. The main objective of this study is to analyse the impact of an ERAS programme for colorectal cancer on 5-year survival. As secondary objectives, we propose to analyse the weight of each of the predefined items in the oncological results as well as the quality of life.Methods and analysis A multicentre prospective cohort study was conducted in patients older than 18 years of age who are scheduled to undergo surgery for colorectal cancer. The study involved 12 hospitals with an implemented enhanced recovery protocol according to the guidelines published by the Spanish National Health Service. The intervention group includes patients with a minimum implementation level of 70%, and the control group includes those who fail to reach this level. Compliance will be studied using 18 key performance indicators, and the results will be analysed using cancer survival indicators, including overall survival, cancer-specific survival and relapse-free survival. The time to recurrence, perioperative morbidity and mortality, hospital stay and quality of life will also be studied, the latter using the validated EuroQol Five questionnaire. The propensity index method will be used to create comparable treatment and control groups, and a multivariate regression will be used to study each variable. The Kaplan-Meier estimator will be used to estimate survival and the log-rank test to make comparisons. A p value of less than 0.05 (two-tailed) will be considered to be significant.Ethics and dissemination Ethical approval for this study was obtained from the Aragon Ethical Committee (C.P.-C.I. PI20/086) on 4 March 2020. The findings of this study will be submitted to peer-reviewed journals (BMJ Open, JAMA Surgery, Annals of Surgery, British Journal of Surgery). Abstracts will be submitted to relevant national and international meetings.Trial registration number NCT04305314.